The Influence Of Mass Media And Human Resource Quality On Public Service Performance In Kendari City (Architecture Image Studies, 2026)
Quality public services are a crucial indicator of the successful implementation of good governance principles, which encompass transparency, accountability, participation, and effectiveness. This study aims to analyze the influence of mass media and the quality of human resources on the performance of public services in the field of education in Kendari City. This study uses a quantitative approach with a survey method to 124 respondents at SMPN & SMPS in Kendari City. Mass media and human resource quality have a positive and significant influence on public service performance with path coefficient values of 0.895 and 0.739, respectively. Mass media have a positive and significant influence on governance. Governance has a positive and significant influence on public service performance, with a path coefficient of 0.955. Public service performance significantly mediates the influence of mass media on governance, with a path coefficient value of 0.739. The quality of human resources on governance through mediation of public service performance shows significant findings with a path coefficient value of 0.833, with a positive relationship direction. Strengthening the role of the media and improving human resource competencies as a strategy in bureaucratic reform, and improving the quality of educational services.